On the resistance of epiphytic cyanobacteria of the Kola Bay to the effects of oil hydrocarbons in the aquatic ecosystem - Pugovkin, Dmitry V.; Miroshnichenko, E.S.; Voskoboinikov, Grigory M.; Jensen, John Beck; Liaimer, Anton (Vestnik MGTU, 2018)
Source at https://doi.org/10.21443/1560-9278-2018-21-2-221-227 . The epiphytic communities of cyanobacteria of Fucus vesiculosus L. of the Kola Bay are able to bear the high amounts of the oil products in the environment. The results of studying the resistance of epiphytic cyanobacterial communities to oil pollution using both classical (cultural) and molecular-genetic methods of microbiological analysis have been presented. The objects of the study are the epiphytic cyanobacterial communities living on the surface of brown algae Fucus vesiculosus L. The percentage of this group of microorganisms in epiphytic bacteriocenosis in the water chronically polluted with oil products reaches 6.8 %. Morphologically epiphytic cyanobacteria are represented by single cells, filaments and colonial forms with small (1–2 µm) cells. The experiments of determining the resistance of epiphytic cyanobacterial communities to oil pollution have been carried out. There is no visible growth during the work with pure cultures of cyanobacteria in media with addition of diesel fuel. In cultures exposed in the dark, there is an increase in the intensity of the blue staining of the filaments. The survival of cyanobacteria in the long period of darkness in the presence of oil products can indicate a transition from autotrophic nutrition to heterotrophic, as well as a high adaptive ability of epiphytic cyanobacterial communities of fucus algae to the conditions of chronic oil pollution. Эпифитные сообщества цианобактерий водорослей Fucus vesiculosus L. Кольского залива способны переносить высокое содержание нефтепродуктов в среде. Представлены результаты исследования устойчивости эпифитных цианобактериальных сообществ к нефтяному загрязнению с использованием как классических (культуральных), так и молекулярно-генетических методов микробиологического анализа. Объектом исследования были эпифитные цианобактерии, обитающие на поверхности бурых водорослей Fucus vesiculosus L. Доля данной группы микроорганизмов в бактериоценозах из акватории с ...